PENGARUH INTELLECTUAL CAPITAL PADA NILAI PERUSAHAAN PERBANKAN - Awaliyah, Novia; Safriliana, Retna (Jurnal Reviu Akuntansi dan Keuangan)
The role of intellectual capital in knowledge-based business is increasingly required. Intellectual capital is belived to contribute to the improvement of frim value. The purpose of this studywas to test empirically the effect of intellectual capital on firm value. Intellectual capital iscalculated by value added intellectual coefficient (VAIC™) and firm value measured by the PriceTo Book Value (PBV) and Earning Per Share (EPS). The population in this study are bankingcompanies listed in Indonesia Stock Exchange during 2011-2015. The number of samples are 24firm that are selected using pourposive sampling method. This study uses observational datafor five periods, so the number of final samples are 120. The data were analyzed using simplelinear regression. The analysis first regression showed that the constants of -0,222 and a significance value of 0.000 which is smaller than á (0.05). This suggests that the positive effect ofintellectual capital on Price Book Value (PBV). And The analysis second regression showed thatthe constants of 0,993 and a significance value of 0.000 which is smaller than á (0.05). Thissuggests that the positive effect of intellectual capital on Earning Per Share (EPS).Ke ywords: Intellectual Capital, Firm Value, value added intellectual coefficient (VAIC™),Price Book Value (PBV), Earning Per Share (EPS).